Liquidity Ratio Analysis and Short-Term Financial Performance: Evidence from PT Garudafood Putra Putri Jaya Tbk (2019–2023) - Devi Vita Lora Saragih; Laily Ramadhani; Hafni Cholida Nasution (Global Insights in Management and Economic Research, 2026)
Purpose of the study: Financial performance assessment is critical for evaluating a company's ability to meet its obligations and sustain operations. Liquidity ratios serve as fundamental indicators of short-term financial health, particularly in the consumer goods industry where working capital management directly impacts operational efficiency and stakeholder confidence. This study aims to analyze and assess the financial performance of PT. Garudafood Putra Putri Jaya, Tbk. during the 2019-2023 period using liquidity ratios comprising the Current Ratio, Quick Ratio, and Cash Ratio, benchmarked against industry standards to determine the company's short-term debt settlement capability. Materials and methods: This research employs a descriptive qualitative analysis approach utilizing secondary data sourced from the audited annual financial statements of PT. Garudafood Putra Putri Jaya, Tbk. obtained from the Indonesia Stock Exchange. The analysis encompasses a five-year longitudinal study period (2019-2023) with financial ratio calculations compared against industry average standards. Results: The findings reveal that the average Current Ratio (165%) and Quick Ratio (101%) fell below industry standards of 200% and 150% respectively, indicating suboptimal short-term liquidity management. Conversely, the Cash Ratio averaged 54%, exceeding the 50% industry benchmark, demonstrating adequate cash reserves for immediate liability coverage. Fluctuations were observed across all ratios during the study period, with notable improvements in 2020 and 2023. Conclusions: PT. Garudafood Putra Putri Jaya, Tbk. demonstrates mixed liquidity performance. While the company maintains satisfactory cash reserves, improvements in current asset management and inventory optimization are recommended to enhance overall liquidity ratios to industry-standard levels, thereby strengthening financial resilience and stakeholder confidence.